Mathematical disposition as a predictor of students’ mathematical communication in solving HOTS-based contextual problems - Arifinta, Hasna Nisa; Wulan, Eka Resti; Yacan, Nurcan (Journal Focus Action of Research Mathematic (Factor M), 2025)
This study examines the influence of mathematical disposition on students’ mathematical communication when solving contextual Higher Order Thinking Skills (HOTS)-based problems. Employing a quantitative ex-post facto design, data were collected from 101 eighth-grade students using a mathematical disposition questionnaire and a mathematical communication test that consisted of contextual HOTS tasks. The results indicate that while many students showed a positive mathematical disposition, their communication performance varied across problem-solving demands. Regression analysis revealed that mathematical disposition contributed to students’ communication, particularly at the analytical level, but its impact diminished as task complexity increased. Overall, disposition played only a modest role in predicting students’ communication in HOTS contexts. The findings suggest that although mathematical disposition enhances students’ willingness to engage with challenging tasks, effective communication at higher cognitive levels also requires stronger conceptual understanding and strategic problem-solving experience. This study highlights the need for instructional approaches that integrate affective and cognitive supports to strengthen students’ mathematical communication in complex, open-ended problem settings.